Experimental Investigation on Bond Strength of Concrete and Steel Bar of Conventional Concrete at Elevated Temperatures - G. , Premkumar; Y. , Lakshmi Pranathi (International Journal of Psychosocial Rehabilitation, 2020)
An experimental investigation is done on the bond strength of reinforcing bars and surrounding concrete at elevated temperatures. The conventional mix M25 is used, and three different types of steel bars of 20 mm diameter are used. A total of 9 pullout specimens are prepared: 3 using plain polished bars, 3 using plain unpolished bars, and 3 using deformed bars. Embedment of the steel bar inside the concrete specimen is done. The pullout specimens are subjected to room temperature and two different elevated temperatures: 100°C and 300°C. Comparisons are done between the different steel bars and temperatures. The results indicated that the pullout specimen with deformed bars at room temperature had the highest bond strength compared to the other bars with different temperatures. The plain bars have shown the least bond strength due to the chemical adhesion and friction. When temperature is taken into consideration, there was a decrease in bond strength for 300°C compared to room temperature. In the deformed bars, there was a decrease of 14.94% when subjected to 300°C. In polished mild steel bars, when subjected to 300ºC, the decrease is 22.46% compared to room temperature. Similarly, in unpolished mild steel bars, there was a decrease of 40.86 %.